The Performance of Trial Covers Used for the Rehabilitation of Acid Generating Coal Reject Dumps in Northern Kwazulu-Natal, South Africa - N Bezuidenhout (The Australasian Institute of Mining and Metallurgy, 2003)
The performances of ten field-scale experimental final covers were evaluated over an eight-year period. The covers were evaluated as part of the rehabilitation of acid generating coarse coal reject dumps and opencast coalmines in the Northern KwaZulu Natal province in South Africa. The main purpose of the experimental covers was to restrict rainfall infiltration into acid generating coal discard. The mean average rainfall over the monitoring period was 839 mm with 84 per cent occurring between October and April. The average evaporation was 2100 mm. The site is described as a ædry siteÆ since the evaporation exceeds rainfall by a significant margin. Approximately 30 per cent of rainfall infiltrated the uncovered cells. Rainfall infiltration into the fine coal discard was reduced to 20 per cent and 15 per cent for a 300 mm and 500 mm cover respectively. Infiltration was reduced to ten and 12 per cent of rainfall for fine coal discard provided with a 1000 mm double soil cover and a compacted bottom layer. This relatively high infiltration was probably caused by moisture being entrapped in the bottom retentive layer, and not being released by evapotranspiration. The best performing cover comprised 1000 mm single soil with a compacted bottom layer and infiltration was reduced to four per cent of rainfall. Rainfall infiltration into sloped cells varied between seven per cent and 14 per cent of rainfall. The computer software, SoilCover, was used to predict infiltration and moisture content in the cover. Predictions of rainfall infiltration were accurate, but were less accurate for covers where the hydraulic properties of field compacted soils were not adequately characterised. Oxygen ingress was significantly reduced for cells provided with a 1000 mm cover. Oxygen concentrations were generally below one per cent, with the exception during exceptionally dry periods when the cover dried out, resulting in increased oxygen ingress. For other covers, and the uncovered cells, oxygen concentrations were close to atmospheric concentrations. During the eight-year monitoring period, acid breakthrough occurred in five of the cells, including three uncovered cells, one cell with a 300 mm cover and one sloped cell. In contrast, cells covered with 1000 mm, bottom compacted soils shows a marked improvement of leachate quality, indicating that sulfide oxidation processes have been slowed. There was a distinct relationship between oxygen ingress and leachate quality for all of the cells. No cover degradation was evident over the eight-year period, except for some erosion observed on a sloped cell. The results indicate that the onset of acid drainage can be delayed by perhaps hundreds of years and salinity loads can be reduced by more than 90 per cent, if coarse coal reject dumps in the KwaZulu-Natal provinces in South Africa are provided by an adequate cover system. These research outcomes can be extrapolated and applied to other dry site regions where similar materials are being considered.